LncRNA NONRATT021972 siRNA regulates neuropathic pain behaviors in type 2 diabetic rats through the P2X7 receptor in dorsal root ganglia. Issue 1 (December 2016) - Liu, Shuangmei; Zou, Lifang; Xie, Jinyan; Xie, Wei; Wen, Shiyao; Xie, Qiuyu; Gao, Yun; Li, Guilin; Zhang, Chunping; Xu, Changshui; Xu, Hong; Wu, Bing; et al.
Abstract Background Long non-protein-coding RNAs (lncRNAs) are involved in the pathological processes of nervous system diseases. NONRATT021972 is an lncRNA. This study explores the effects of lncRNA NONRATT021972 small interference RNA (siRNA) on diabetic neuropathic pain (DNP) mediated by the P2X7 receptor in the rat dorsal root ganglia (DRG). Results Our results show that NONRATT021972 expression was significantly higher in the DRG of diabetes mellitus (DM) group compared with control group. NONRATT021972 expression in the DRG was reduced when DM rats were treated with NONRATT021972 siRNA. NONRATT021972 siRNA treatment in type 2 DM rats increased the mechanical withdrawal threshold (MWT), the thermal withdrawal latency (TWL) and the sensory nerve conduction velocity (SNCV) of rat tail nerves. After intravenous injection with NONRATT021972 siRNA in DM rats, the P2X7, GFAP and TNF-ɑ expression levels in DRG were decreased. An interaction between the RNA (NONRATT021972) and protein (P2X7 ) was predicted by the application of bioinformatics technology. The BzATP-activated currents in DRG non-neurons (satellite glial cells) of DM rats were significantly increased compared to control rats. NONRATT021972 siRNA treatment inhibited the ATP-activated currents in HEK293 cells transfected with pEGFP-P2X7 . Conclusions NONRATT021972 siRNA treatment can decrease the expression levels of P2X7 mRNA and protein and inhibit the activation of satellite glial cells (SGCs) in the DRG of type 2 DM rats. Moreover, NONRATT021972 siRNA treatment reduced the release of inflammatory factors (TNF-α), thereby inhibiting the excitability of DRG neurons and reducing mechanical and thermal hyperalgesia in type 2 DM rats.